Study on the metabolic process of phthalic acid driven proliferation of Rhizoctonia solani - Ju, Jidong; Zhou, Bingqian; Yang, Guohong; Fu, Xinyu; Wang, Xiao; Guo, Lanping; Liu, Wei (Frontiers in Plant Science, 2023)
Introduction Continuous cropping obstacle seriously affects the quality and yield of Salvia miltiorrhiza, and the synergistic effect of root exudates and rhizosphere pathogenic microorganisms may be an important cause of continuous cropping obstacle. This study aimed to explore the effects of representative organic acids on the growth and metabolism of specific microorganisms in the S. miltiorrhiza rhizosphere soil under continuous cropping, and clarify its mechanism. Methods The effect of phthalic acid (PA) on the growth and metabolism of Rhizoctonia solani was evaluated by mycelial growth inhibition method. Ultra-high performance liquid chromatography and tandem mass spectrometry were used to identify the differential metabolites of R. solani induced by exogenous PA. Results PA exerted a concentration-dependent effect on mycelial growth, biomass, intracellular polysaccharides con-tent, and total protein content in R. solani. A total of 1773 metabolites and 1040 differential metabolites were identified in the blank medium (CK), Fungi (CK + fungi), and PA-Fungi (CK + fungi + acid) groups. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis showed that the differential metabolites were mainly involved in the sugar, lipid, and protein metabolic pathways related to stable membrane structure and cell growth. Discussion The proliferation and metabolism network of R. solani induced by PA was proposed, and the enhancement of sugar, lipid, and amino acid metabolism was presumed to be related to the active resistance of cells to organic acid stress. These results offer new in-sights into the effects of PA metabolism on promoting R. solani proliferation, and provide theoretical support for further optimizing the rhizosphere microecological environment of Salvia miltiorrhiza continuous cropping soil and reducing continuous cropping obstacle.